Grammatik der slavischen Sprache in Krain, Kärnten und Steyermark (1808) Jerneja Kopitarja in Primož Trubar - Orel, Irena (Slavistična revija, 2008)
On the occasion of Primož Trubar's 500th birthday and the 200th anniversary of Kopitar's grammar, the author thorougly analyzes and re-examines the eminent Slovene Slavist's views of the founder of Slovene literary language in terms of alphabet, orthography, grammar, and historical linguistics, in his Grammatik der Slavischen Sprache in Krain, Kärnten und Steyermark (Laibach 1808), as is evident from his statements, quotes, and opinions and confirmes by excerpts from Trubar's texts. Trubar's linguistic and literary contribution must be understood in the first Slovene scholarly grammarian from the beginning of the 19th century it cannot be overlooked, despite the notorious negative opinions concerning Trubar's choice of alphabet and excessive germanization.
Keywords: knjižni jezik; Kopitar, Jernej; slovenščina; slovnica; Trubar, Primož; zgodovina jezika